Wireless Insights Into Cognitive Wellness: A Paradigm Shift in Alzheimer's Detection Through Ultrathin Wearable Antennas - Taher, Fatma; Alathbah, Moath; Abdel-Aleim M., M.; Alghamdi, Thamer; Sree, Mohamed Fathy Abo; Fatah, Sara Yehia Abdel (IEEE access, 2024)
The Proposed algorithm, designed to simulate an Alzheimer's disease (AD) brain model across different stages, presents an invaluable opportunity for further research and in-depth study of the effects of AD. Currently, there is a notable absence of a comprehensive simulated model for the AD brain that allows the exploration of all AD biomarkers within a simulation tool. This represents a crucial advancement in the field, enabling researchers to thoroughly investigate and understand the diverse biomarkers associated with AD without resorting to highly expensive and ionizing radiation techniques. The algorithm's capability to emulate various stages of AD in a simulated environment is an essential step toward assessing its applicability for AD patients, providing a cost-effective and safer alternative for research and study in comparison to existing methodologies and delves into the development and evolution of a patch antenna designed for the identification of distinct stages in Alzheimer's disease (AD) detection. The antenna, equipped with ultra-wideband (UWB) capabilities, consists of a slotted circular disc antenna patch and a partial ground. The placement of rectangular slots in the ground structure aims to enhance radiation directivity, gain, and efficiency. The primary objective is to optimize the antenna's efficacy by strategically integrating a slotted circular disc and arranging slots in the ground structure. The research aims to provide an effective solution for non-invasive tracking of Alzheimer's disease progression. The antenna, with dimensions of 50× 35× 0.1 mm3, is fabricated using a flexible laminate substrate (Ultra-lam 3850). The prototype demonstrates a remarkable bandwidth of 8.55 GHz (2.02-10.57 GHz) and exhibits nearly directional radiation characteristics. The study employs 3D CST 2019 simulator software for analysis, followed by physical fabrication and measurement of the antenna. Evaluation involves both a single antenna and a four-antenna array element around a 3D realistic-shaped Hugo head model and a six-layer brain phantom simulating various AD stages. The reported peak gain reaches 2.36 dBi and 3.1 dBi at 2.4 GHz and 7.48 GHz, respectively, with consistently high radiation efficiency (92.5% and 90.5% at 2.4 GHz and 7.48 GHz).